2021
DOI: 10.1111/obr.13260
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of screen time among young children aged 0–6 years: A systematic review

Abstract: The impact of screen-based devices on children's health and development cannot be properly understood without valid and reliable tools that measure screen time within the evolving digital landscape. This review aimed to summarize characteristics of measurement tools used to assess screen time in young children; evaluate reporting of psychometric properties; and examine time trends related to measurement and reporting of screen time. A systematic review of articles published in English across three databases fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
42
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(60 citation statements)
references
References 611 publications
5
42
0
4
Order By: Relevance
“…Almost all interventions (97%) measured screen time via self- or parent-report. These findings are consistent with a recent review that reported that no articles used an objective, device-based tool to measure screen time in children 6 years old or younger [ 244 ]. Interventions that objectively measured screen time were associated with larger, albeit non-significant effects, compared to interventions that measured screen time via self- or parent-report.…”
Section: Discussionsupporting
confidence: 92%
“…Almost all interventions (97%) measured screen time via self- or parent-report. These findings are consistent with a recent review that reported that no articles used an objective, device-based tool to measure screen time in children 6 years old or younger [ 244 ]. Interventions that objectively measured screen time were associated with larger, albeit non-significant effects, compared to interventions that measured screen time via self- or parent-report.…”
Section: Discussionsupporting
confidence: 92%
“…Findings of this study show that Irish children spend an average of 155 min in front of a screen daily for leisure activities. This compares with 91-120 min reported by Healy et al [57] for typically developing Irish children. O'Brien et al [14] reported a much higher average screen time of (2.65 h) in eight-year-old Irish children; however, notably this study focussed on children from areas of social disadvantage, with children from lower socioeconomic background known to be of higher risk of negative health impli-cations associated with increased screen time [2].…”
Section: Discussionsupporting
confidence: 63%
“…К сожалению, в большинстве этих исследований изучали влияние на детей раннего возраста исключительно телевидения. Лишь с 2015 г. наблюдается заметное увеличение доли статей, в которых описаны результаты исследований воздействия мобильных устройств [3].…”
Section: экранное время и познавательное развитие в раннем детствеunclassified